PCB Design & Fabrication For Begineers - M. F., Abas (Penerbit Universiti Malaysia Pahang, 2007)
PCB (Printed Circuit Board) design is quite a tedious process unless an understandable manual is available. To overcome this predicament, the author has decided to embark on a journey to compose this simple but subtle book on how to design and fabricate a PCB. This book is not for the advance PCB developer since a lot of advance material has been removed to make this book easy and understandable to those who are not familiar with PCB design and fabrication but has the ergs to take the first step. This book does not handle simulation since simulation books are very common in the market.